Diagnóstico de biodigestor em escala real de um abatedouro de bovinos em Francisco Beltrão - Moreschi, João Vitor (2023)
Brazil has stood out in the use of renewable energy sources. One such source is biogas, which can be generated in a number of ways including anaerobic digestion of waste. Thinking about improving the performance of the anaerobic digestion process, the objective of this work was to monitor a CSTR model biodigester (Continuous Stirred Tank Reactor) installed in a bovine slaughterhouse. The biogas generated is used to generate electricity, which is sold to the electricity company, thus providing an extra financial source for the company. The monitoring focused on analyzing the input and output parameters of the biodigester, analyzing the physical and chemical measurements of the effluent, such as: total solids, fixed and volatile, oils and greases, the removable volumetric organic load in the biodigester, the total Kjedahl carriers and ammoniacal, a relationship between protected alkalinity and partial alkalinity and the quality of the generated biogas. With the results obtained in the analyses, it was possible to identify that the biogas generated by the biodigester has a good quality for burning and generating clean electricity. It can also be observed that there is no significant number of fixed solids or oils and greases inside the biodigester, indicating that the biodigester is functioning as expected. With this, it was possible to identify and pass on to the company possible improvements in the process of the biodigester, so that the production of biogas is perfected, and with that, the possible growth in the production of biogas for the generation of electric energy, bringing with it a financial return in the sale of electricity.